Evaluating different soil amendments as bioremediation strategy for wetland soil contaminated by crude oil - Jumbo, Raphael; Coulon, Frederic; Cowley, Tamazon; Azuazu, Ikeabiama; Atai, Emmanuel; Bortone, Imma; Jiang, Ying (MDPI, 2022)
This study evaluated the efficacy of using Tween 80 surfactant (TW80) and food-waste anaerobic digestate fibre (FWAD) as soil amendments for the remediation of wetlands contaminated by crude oil. A 112-day mesocosms experiment was carried out to simulate hydrocarbon degradation under typical acidified wetland conditions. Soil was spiked with 50,000 mg kg−1 crude oil and TW80 and FWAD were added to mesocosms at 10%, 20% and 30% w/w. The soil basal respiration, microbial community dynamics, environmental stress, alkanes, and PAHs degradation were monitored throughout the mesocosm experiment. Amending the mesocosms with FWAD and TW80 enabled the recovery of the soil microbial activities. This was evidenced by soil basal respiration which was the highest in the 30% FWAD and 30% TW80 mesocosms and translated into increased degradation rate of 32% and 23% for alkanes, and 33% and 26% for PAHs compared to natural attenuation, respectively. Efficient total hydrocarbon degradation was achieved in soil mesocosms with 30% FWAD and 30% TW80 at 90% and 86.8%, respectively after 49 days. Maize seed germination results showed significant improvement from 29% to over 90% following the FWAD and TW80 treatment.
Keywords: remediation; wetlands; food-base digestate; surfactant; hydrocarbons